Narrative, Insecure Equilibrium and the Imperative to Understand: A Hermeneutics of Woundedness - Małgorzata Hołda (Lodz University Press, 2021)
Addressing trauma as a phenomenon which happens on the level of the human psyche and body, this article explores the impact of the interlocking nature of human lingual and bodily being in discovering a fuller possibility of interpreting and understanding woundedness. The non-transparent and problematic character of trauma calls for a hermeneutic investigation in order to gain a far-reaching insight into what happens with us and in us in traumatic experience(s). The imperative to understand the situation of affliction is an unending task which not only relies upon extant understandings but continually pro-vokes new ones. I argue that the process of healing, encompassing the spoken and bodily narrative, does not establish a secure equilibrium, but rather searches for self-restoring, healing energy and commences ever new understandings of what needs to be comprehended and healed. This article offers an examination of trauma as featured in three short stories by British authors: Rudyard Kipling, D. H. Lawrence and James Joyce, to exemplify the possibilities of literature to shed light on the intricate nature of traumatic experience. It interrogates the ways in which literature, hermeneutics and psychoanalysis meaningfully converge.